EFEKTIVITAS PEMBELAJARAN MATEMATIKA DENGAN HYPNOTEACHING TERHADAP PRESTASI MAHASISWA PADA MATA KULIAH GEOMETRI II IKIP PGRI BOJONEGORO - Safitri, Dian Nurul; Purnamasari, Nelly Indriastuti (JURNAL e-DuMath, 2017)
The purpose of this research was to determine the effectiveness of mathematics learning by hypnoteaching on student achievement in the subject of geometry II. This research used quantitative approach and including a quasi-experimental research because it is not possible to control all the variables that affect the dependent variable. Population in this study were all students of sixth semester in third grade mathematics department FPMIPA IKIP PGRI Bojonegoro. Sample in this study were obtained by simple random sampling. Documentation methods used to retrieve data final exam and test techniques are used to determine students achievement in the subject geometry II. Whereas for data analysis techniques in this study using several statistical tests, among others, the prerequisite test were normality test using Liliefors and homogeneity test with f test, and balance testing with two-tailed t-test and hypothesis using one tailed t-test. After conducting research and analysis with one tailed t test on students learning achievement on the geometry subject can be concluded that hypnoteaching learning gives better achievement than direct instruction. So it can be concluded that the hypothesis presented by researchers indicate that learning hypnoteaching gives a better achievement than the direct instruction.